REVOLUSI HIJAU DI DESA KEMANTAN KEBALAI KECAMATAN AIR HANGAT TIMUR KABUPATEN KERINCI DAN PERUBAHAN TERHADAP KEHIDUPAN PETANI (1969-1998) - Ayesma, Pamela - (Pendidikan Sejarah, 2014)
This thesis discusses (1) How does the entry process and the implementation of the GreenRevolution in the Village Kemantan Kebalai years 1969-1998 and (2) What is the impact of theGreen Revolution on the lives of farmers in the village Kemantan Kebalai years 1969-1998. Thisstudy aims to explore and describe (1) the entry process and the implementation of the GreenRevolution in the Village Kemantan Kebalai years 1969-1998. (2) Impact of the Green Revolutionon the lives of farmers in the village Kemantan Kebalai years 1969-1998. This research includesthe study of history: (1) Heuristic, (2) Source critic, (3) Analysis and interpretation, (4)Historiography. Based on the results of research to the field that the Green Revolution wasintroduced to the people of the village Kemantan Kebalai 1972 by Mr. Udin Hasanuddin(Agricultural Extension Officer) and some community leaders such as village chief, Babinsa,police chief, and the sub-district. Early implementation Guidance programs face many obstacles,such as lack of interest of farmers to change traditional farming systems to more advancedfarming. PPL approximately ten years to convince villagers to accept Kemantan Kebalai Guidanceprogram. 1982 Guidance program has been started in the village received by most peopleKemantan Kebalai, society has begun to change the old agricultural systems to modern agriculture.This farming system changes impact on the socio-economic life of the community that is able toincrease incomes and improve the welfare of society. Other changes are perceived by thecommunity of social and cultural systems start to fade and the impact on the lives of thesurrounding environment.